Sosialisasi Cara Pencegahan dan Penularan Penyakit Tuberkulosis serta Upaya Peningkatan Mikroelemen Tubuh bagi Penderita Tuberkulosis - Latifah, Aminahtun; Kurniasih, Dewi; Muslina, Muslina; Armizan, Eka Wira (Pusat Penelitian dan Pengabdian kepada Masyarakat, Politeknik Kesehatatan Kemenkes Palembang, 2022)
Tuberculosis is an infectious disease suffered by Indonesian people. The increase in cases of TB disease is caused by several factors, namely the lack of public knowledge about ways of transmission and prevention of TB disease, lack of supervision and disobedience of patients in taking anti-tuberculosis drugs. In addition, as a result of taking anti-tuberculosis drugs, it can lead to malnutrition or mineral deficiencies in the body of TB sufferers. To overcome this problem, counseling is carried out on methods of transmission and prevention in order to avoid TB disease and how to monitor TB sufferers when taking anti-tuberculosis drugs. In addition, counseling was also carried out on how TB sufferers can improve their health (nutritional status) as a result of taking anti-tuberculosis drugs. After this community service activity, the results showed that there was an increase in the knowledge and attitude/behavior of respondents regarding pulmonary TB disease, both regarding the causes of pulmonary TB disease, symptoms, methods of transmission, prevention and how to improve or improve the nutritional status of TB sufferers.